2017
DOI: 10.1063/1.4981258
|View full text |Cite
|
Sign up to set email alerts
|

Polymer and spherical nanoparticle diffusion in nanocomposites

Abstract: Nanoparticle and polymer dynamics in nanocomposites containing spherical nanoparticles were investigated by means of molecular dynamics simulations. We show that the polymer diffusivity decreases with nanoparticle loading due to an increase of the interfacial area created by nanoparticles, in the polymer matrix. We show that small sized nanoparticles can diffuse much faster than that predicted from the Stokes-Einstein relation in the dilute regime. We show that the nanoparticle diffusivity decreases at higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 113 publications
5
65
1
Order By: Relevance
“…Liu et al [27] have observed a reduction of the NP diffusion coefficient with increasing φ N , and attributed the phenomenon to polymer-mediated interactions, i.e., to the formation of chain bridges between neighboring NPs that would hinder NP motion; it is not clear, however, what the typical lifetime of such bridges should be, and thus whether this explanation is correct. Karatrantos et al [32] have observed a similar reduction in NP mobility and argued that it is due "to both nanoparticle-polymer surface area and nanoparticle volume fraction" [32], implying that pure geometry and polymer-NP attraction both play a role. The importance of polymer-NP interaction in NP dynamics is beyond dispute: Patti [29] showed that the diffusion coefficient of NPs in an unentangled melt decreases monotonically when the strength of the polymer-NP interaction is increased, with the decrease being stronger for smaller NPs.…”
Section: Nanoparticle Diffusionmentioning
confidence: 94%
“…Liu et al [27] have observed a reduction of the NP diffusion coefficient with increasing φ N , and attributed the phenomenon to polymer-mediated interactions, i.e., to the formation of chain bridges between neighboring NPs that would hinder NP motion; it is not clear, however, what the typical lifetime of such bridges should be, and thus whether this explanation is correct. Karatrantos et al [32] have observed a similar reduction in NP mobility and argued that it is due "to both nanoparticle-polymer surface area and nanoparticle volume fraction" [32], implying that pure geometry and polymer-NP attraction both play a role. The importance of polymer-NP interaction in NP dynamics is beyond dispute: Patti [29] showed that the diffusion coefficient of NPs in an unentangled melt decreases monotonically when the strength of the polymer-NP interaction is increased, with the decrease being stronger for smaller NPs.…”
Section: Nanoparticle Diffusionmentioning
confidence: 94%
“…However, further CNT addition continues to increase the interfacial area between the polymer and CNT, thus enhancing storage modulus. Recent simulation efforts from Clarke and co‐workers showed a similar effect; namely, that increasing the polymer‐nanoparticle interfacial area decreases the polymer diffusivity . This finding is important for designing composites, recognizing that the storage modulus can be tailored independent of the T g to some extent.…”
Section: Resultsmentioning
confidence: 80%
“…However, such approach is very computationally expensive and would increase an order of magnitude the computational cost [46]. Using such a molecular simulation methodology, we can easily tune to carbons of different physical and chemical properties or different organic solvents to extrapolate ion storage, diffusion [47] and, capacity under charge/ discharge cycles [48] and under operating conditions.…”
Section: Discussionmentioning
confidence: 99%